KLASIFIKASI ECHINOIDEA (FILUM ECHINODERMATA) DENGAN METODE TAKSONOMI NUMERIK-FENETIK - Zahratul Idami (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2019)
Echinoidea (Phylum Echinodermata) is an aquatic biota that has economic value both economic and ecologic. Echinoidea has the characteristics of thorns which can be used as one of the characters in identification and classification. One of classify Echinoidea is to use the numerical-phenetic method. This method was groups each species according to the morphological similarities observed and account. This study aims to determine the types of Echinoidea and its important to grouping because it has important economic value in the fisheries sector and in conducting the data collection of Echinoidea biodiversity. This study used 7 species of Echinoidea namely Tripneustes sp., Euchinotrix sp., Euchinometra sp., Diadema sp., Stomopneustes sp., Heterocentrotus sp., and Colobocentrotus sp. This study used descriptive qualitative method. Analysis data used MVSV 3.1 application for similarity matrix (Simple Matching Coefficient and Jacard Coefficient) and dendogram. The results showed thorns as a characteristic in the classification of Echinoidea. Echinoidea classification shows two groups that have the highest value, namely Euchinotrix sp., And Diadema sp with 80% similarity value and Colobocentrotus sp with Echinometra, sp which is 76% (Simple Matching Coefficient). Whereas based on Jacard Coefficient the two groups have the same similarity value of 53%. Keywords: numeric-fenetic, echinoidea, similarity